Language rights, indigenous cultures and intercultural education in the Brazilian and Polish contexts: approaches to additional language teaching - Samuel Figueira-Cardoso (Revista Educação e Políticas em Debate)
This paper examines linguistic diversity in Brazil and Poland, focusing on the status of indigenous languages and the teaching of additional languages, such as Portuguese, under an intercultural approach (Baniwa, 2013; Kayapó, 2019). The research starts from the conception of language as a historical and social phenomenon (Marcuschi, 2008), analyzing language rights in both countries (Pisarek, 2011; Rodrigues, 2015; Maher, 2016; Szwajczuk, 2013; Przybyła-Wilkin, 2021) and reflecting on the incorporation of these languages into the educational context, with special attention to the training of Brazilian Studies students at Polish universities (Figueira-Cardoso, 2021; 2023). Based on an interpretivist qualitative analysis, anchored in a literature review and document analysis (Cellard, 2008; Lüdke; André, 2022; Paiva, 2019), the study compares the Polish and Brazilian contexts, addressing the role of indigenous and intercultural school education in building a pluri-multilingual society. The defense of an education that considers cultural and linguistic diversity is central, highlighting the urgency of curricula that respect the realities of indigenous communities and promote a transformative and inclusive education. The article concludes by suggesting the incorporation of these themes into the teaching of Portuguese as an additional language, both in Brazil and in foreign universities, with a view to strengthening interculturality and cultural sustainability.